Civil Society and Gender Relations in Authoritarian and Hybrid Regimes : New Theoretical Approaches and Empirical Case Studies - Wilde, Gabriele; Zimmer, Annette; Obuch, Katharina; Panreck, Isabelle-Christine (2018)
Is civil society's influence favorable to the evolvement of democratic structures and democratic gender relations? While traditional approaches would answer in the affirmative, the authors highlight the ambivalences. Focusing on women's organizations in authoritarian and hybrid regimes, they cover the full spectrum of civil society's possible performance: from its important role in the overcoming of power relations to its reinforcement as backers of government structures or the distribution of antifeminist ideas.